Penguatan Nilai-Nilai Toleransi Beragama Melalui Kegiatan Peace Camp - Maulani, Rayfan Ade; Maula, Ismatul; Sari, Meutya Vianda; Anbiya, Bakti Fatwa (Jurnal Riset Agama, 2024)
This research aims to examine the strengthening of tolerance values through peace camp activities. The method used in this research is qualitative with an analytic descriptive approach. Data collection techniques were conducted through literature study and interviews with participants of the peace camp held in Salatiga city in March 2024. This study found that there are five values of religious tolerance contained in this activity, including respect for differences, the existence of open interfaith dialog, the emergence of cooperation in diversity, the existence of empathy and concern between religious communities, and peace education. These values can create an inclusive environment where religious people can practice their beliefs freely, but social harmony is maintained.